Structural variety in zinc telluro-phosphates: syntheses, crystal structures and characterizations of Sr2Zn3Te2P2O14, Pb2Zn3Te2P2O14 and Ba2Zn2TeP2O11. Issue 17 (5th April 2016) - Xia, Mingjun; Li, R. K.
Abstract : Three zinc telluro-phosphates, Sr2 Zn3 Te2 P2 O14, Pb2 Zn3 Te2 P2 O14 and Ba2 Zn2 TeP2 O11, exhibit various topological crystal structures due to their diversity of Te–O groups and alkaline earth/lead elements. Abstract : Three new zinc telluro-phosphates, Sr2 Zn3 Te2 P2 O14 (1 ), Pb2 Zn3 Te2 P2 O14 (2 ) and Ba2 Zn2 TeP2 O11 (3 ), were grown by flux method, and their crystal structures were solved by X-ray diffraction method. Although all three crystals crystallize into the same space group P 21 / c with similar chemical compositions, they exhibit different topology structure types.1 features a two-dimensional layered structure with the connection of TeO4 and (Zn3 TeP2 O18 ) 16− 12-membered rings (MRs), which are composed of planar square and tetrahedral configuration ZnO4 groups, tetrahedral PO4 and seesaw TeO4 . Due to lone-pair Coulomb repulsion of Pb 2+, the structure of2, which is also composed of unbalanced seesaw TeO4 and ZnO4 groups and distorted PO4 tetrahedra, is slightly different from that of its analog1 . Compound3 exhibits a complicated three-dimensional network with (Zn2 PO9 ) 9− 6-MRs and (Zn2 Te2 O10 ) 8− 8-MRs built from distorted tetrahedral ZnO4 and PO4 groups and trigonal pyramidal TeO3 units. According to UV-vis-NIR diffuse reflectance spectra, compounds1, 2 and3 are highly transparent in the range of 450 to 2500 nm with a UV cut-off of 275 nm, 330 nm and 278 nm, respectively. In addition, the characterizations, including thermal analyses, XPS measurement and dipole moment calculations, are also reported.